(untitled) (Papeles, 2021)
Part of the results of a classroom experience that takes theoretical foundations from a proposal for ICT incorporation are presented, under a model of development of cognitive linguistic skills, through the teaching of structuring concepts of chemistry. As a practical exercise of intervention in the classroom, this work proposed to apply a methodology of "Didactic Design with ICT Incorporation", with the aim of achieving better learning in students, offering alternative scenarios of scientific-scholar education in the non-face-to-face modality, caused by the health crisis of COVID-19. Taking methodological aspects of the action-research, instruments were developed to understand the emerging needs of ICT incorporation, due to the withdrawal of the school population from the classrooms, participant intervention was carried out to address the difficulties of the proposed methodology and achieve efficient solutions. Among the findings the need to promote training processes in ICT for teachers, to face educational technological challenges, generate digital skills in students of public institutions in the city of Bogotá and recognize alternative didactic design approaches that allow to overcome specific problems of science education mediated by ICT.